(untitled) (Journal of Human Sciences, 2025)
This work aims to shed light on an important period of Mauritanian history, focusing on its cultural, civilizational, and scientific aspects. The study centers on one of the caravan cities that emerged in Mauritania, which, throughout its long history, remained a hub of cultural and scientific influence. Specifically, it focuses on the city of Walata, which stands as a living example of the rich civilizational, cultural, and scientific heritage characteristic of Mauritania’s desert cities. Through this research, we sought to highlight the scientific and cultural significance of this city, whether through its renowned scientific contributions or its cultural and intellectual influence within its nearby desert surroundings and wider regional context.